(untitled) (Research, Society and Development, 2022)
Objective: to investigate the scientific production in relation to the quality and the means of communication of the nursing professional with the patient with hearing loss. Methodology: This is an integrative review study, with a qualitative approach of the descriptive type. For the construction of the integrative review, six different stages were used, defined by Ursi (2005). Results: From the data collected, the results were organized into 4 categories: means of communication, experience of the nursing professional, experience of the patient with hearing loss in the health unit and suggestions for a humanized reception. Conclusion: it was concluded that nursing professionals have difficulties that hinder the care of patients with hearing loss and they feel discriminated against and excluded for not being able to enjoy an effective reception in the same way as the hearing population. Therefore, alternative communication needs to be stimulated so that these patients are treated in a way that communication is efficient. It is essential that strategies are designed so that the deaf population has their right to health guaranteed.